Influence of performance appraisal system on overall climate of agricultural extension organizations - Souvik Ghosh,; K. Vijayaragavan, (Journal of Agricultural Extension Management, 2025)
In the entire process of individual development and organisational effectiveness, performance appraisal plays a vital role. Performance appraisal mechanism is intended to maintain a satisfactory level of work environment, job performance and employee development in the organisation (Rao, 1992). Employee growth and satisfaction with the job, individual productivity improvement and overall climate in an organisation are expected to be influenced by the performance appraisal system (PAS) in operation. A positive approach towards performance appraisal results in higher productivity (Kumar et al., 1993). Considering that the quality of the human resource in an agricultural extension organization is a determining factor in its success or failure, performance appraisal is a critical management function and an effective way to improve performance of extension personnel (Davis, 1993). The effectiveness of extension workers in promoting and speeding up the dissemination of new agricultural practices depends on the interaction factors between organizational climate and performance appraisal system. With the ever increasing complexity of challenges facing extension organizations, extension personnel need to play proactive and strategic partner roles. Keeping these above-mentioned facts in view, the present study aims to assess the performance appraisal system and organisational climate along with exploring the relationship between them